2003
DOI: 10.1017/s0952523803201061
|View full text |Cite
|
Sign up to set email alerts
|

How long range is contour integration in human color vision?

Abstract: We quantified and compared the effect of element spacing on contour integration between the achromatic (Ach), red-green (RG), and blue-yellow (BY) mechanisms. The task requires the linking of orientation across space to detect a contour in a stimulus composed of randomly oriented Gabor elements (1.5 cpd, s ϭ 0.17 deg), measured using a temporal 2AFC method. A contour of ten elements was pasted into a 10 ϫ 10 cells array, and background elements were randomly positioned within the available cells. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 81 publications
(145 reference statements)
5
42
0
Order By: Relevance
“…Their results showed that the minimum aspect ratio required to discriminate an ellipse from a circle decreased with increasing contour sampling at the same rate for younger and older subjects. Interelement spacing has also been shown to affect the detectability and discriminability of elongated contours embedded in cluttered backgrounds (e.g., Beaudot & Mullen, 2003;Kovács & Julesz, 1993;Li & Gilbert, 2002). Interestingly, similar to the current results, the effect of interelement spacing on contour grouping was the same in younger and older subjects (Hadad, 2012;Roudaia et al, 2013), even though overall ability to detect and discriminate contours in noise declines with aging (Del Viva & Agostini, 2007;Roudaia et al, 2011Roudaia et al, , 2013.…”
Section: Discussionsupporting
confidence: 77%
“…Their results showed that the minimum aspect ratio required to discriminate an ellipse from a circle decreased with increasing contour sampling at the same rate for younger and older subjects. Interelement spacing has also been shown to affect the detectability and discriminability of elongated contours embedded in cluttered backgrounds (e.g., Beaudot & Mullen, 2003;Kovács & Julesz, 1993;Li & Gilbert, 2002). Interestingly, similar to the current results, the effect of interelement spacing on contour grouping was the same in younger and older subjects (Hadad, 2012;Roudaia et al, 2013), even though overall ability to detect and discriminate contours in noise declines with aging (Del Viva & Agostini, 2007;Roudaia et al, 2011Roudaia et al, , 2013.…”
Section: Discussionsupporting
confidence: 77%
“…Subject performance was measured as a function of interelement angle in a 2AFC paradigm. This experimental approach has proven very popular in subsequent studies (reviewed by Field, 1999, andField, 2003) in which a large number of local or global stimulus properties have been assessed, such as contour closure (Kovacs & Julesz, 1993), polarity and luminance contrast along the path (Field, Hayes, & Hess, 2000), chromaticity and color contrast (Beaudot & Mullen, 2003;McIlhagga & Mullen, 1996), spatial frequency tuning , eccentricity (Hess & Dakin, 1999;Nugent, Keswani, Woods, & Peli, 2003), temporal properties of the presentation (Beaudot, 2002;Hess, Beaudot, & Mullen, 2001), and stationary motion (Bex, Simmers, & Dakin, 2001). Most relevant in the context of this article is the consistent finding that contour saliency increases with element alignment and proximity.…”
Section: Current Approaches To Groupingmentioning
confidence: 99%
“…Perception studies [BM03,EM98] show that long coherent-edges are perceptually salient to the HVS even they are faint. Long edges may reveal the important information about the object.…”
Section: Structural Edge Constraintmentioning
confidence: 99%
“…The importance of edges is considered using the Gaussian scale space analysis to ensure the structures of the objects are preserved through camouflage manipulations. Perception research [BM03,EM98] shows that long coherent-edges, even when faint, are perceptually salient to the human visual system (HVS). Motivated by the law of closure of Gestalt psychology's theory, which states that humans perceive objects as a whole even when they are not complete, we take long and important edges of the object into account, and divide these edges into shorter edges and remove some of them.…”
Section: Introductionmentioning
confidence: 99%